Optimasi Implementasi Sound Absorption (Insulasi Suara) Pada Bagian Bulkhead Bus - Marcello Sintong Bona Parulian Sihaloho (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study discusses noise control in buses through the optimization of sound-absorbing materials used on bulkheads, which are the dividing walls between the driver and passenger compartments. The testing was conducted using various materials such as aluminum foam, glass wool, and polyurethane foam, as well as variations in the thickness of glass wool (2.5 cm and 5 cm) in both open and closed test box conditions. The results showed that glass wool with a thickness of 5 cm had a higher sound absorption effectiveness, with a sound intensity reduction of up to 28.5 dB and an effectiveness of 34.9%. The study also identified the advantages and disadvantages of each material, including aluminum foam, which is lightweight, strong, and corrosion-resistant but expensive, and glass wool and polyurethane foam, which are cost-effective but have durability limitations. In addition to acoustics, the study considered cost factors, environmental resistance, and production processes. In conclusion, the selection of material and bulkhead design must be carefully made to optimize acoustic performance, comfort, and cost efficiency in noise reduction in buses. Keywords: Sound Absorption, Bus Bulkhead, Glass Wool, Acoustics, Polyurethane Foam AbstrakPenelitian ini membahas pengendalian kebisingan pada bus melalui optimasi penggunaan material penyerap suara pada bulkhead, yaitu dinding pemisah antara ruang pengemudi dan penumpang. Pengujian dilakukan dengan menggunakan berbagai material seperti alumunium foam, glass wool, dan polyurethane foam, serta variasi ketebalan glass wool (2,5 cm dan 5 cm) pada kotak uji dengan kondisi terbuka dan tertutup. Hasil pengujian menunjukkan bahwa glass wool dengan ketebalan 5 cm memiliki efektivitas penyerapan suara lebih tinggi, dengan reduksi intensitas bunyi mencapai 28,5 dB dan efektivitas 34,9%. Penelitian juga mengidentifikasi kelebihan dan kekurangan masing-masing material, di antaranya alumunium foam yang ringan, kuat, dan tahan korosi namun berbiaya tinggi, serta glass wool dan polyurethane foam yang ekonomis namun memiliki keterbatasan durabilitas. Selain aspek akustik, penelitian mempertimbangkan faktor biaya, ketahanan lingkungan, dan proses produksi. Kesimpulannya, pemilihan material dan desain bulkhead harus dilakukan secara cermat untuk mengoptimalkan performa akustik, kenyamanan, dan efisiensi biaya dalam pengurangan kebisingan pada bus. Kata Kunci: Sound Absorption, Bulkhead Bus, Glass Wool, Akustik, Polyurethane Foam